PENGARUH PEREBUSAN DAN PEMADATAN TERHADAP SIFAT FISIS DAN ANATOMI KAYU JABON (Anthocephalus cadamba) - Meylida Nurrachmania; Rozalina (BRIN Publishing, 2021)
One way to improve the quality of low-quality wood is by means of wood densification techniques or wood compaction by boilingmethod. This study observes the effect of boiling and densification on the physical and anatomical properties of jabon wood(Anthocephalus cadamba). Boiling is carried out for 60 and 120 minutes using jabon wood (Anthocephalus cadamba)measuring 10 cm x 5 cm x 2 cm on tangential boards (perpendicular to the tree), then the wood is hot pressed at temperature170°C for 3 minutes with a compaction target of 50% of the initial thickness. Data were analyzed descriptively.Results show thatthe recovery of set value for control is 64.93%; 69.99% for the 60 minutes boiled samples and 78.17% for those the 120 minutesboiled samples. Density after treatments were 0.58, 0.56, and 0.60gr/cm3respectively for control, boiled 60 minutes and boiled120 minutes. Pressing at high temperature (170°C) on the treated wood samples do not cause serious damage onanatomicalproperties of the compressed wood but changes color due to high temperature.